Subthalamic Nucleus Deep Brain Stimulation in Early Stage Parkinson’s Disease Is Not Associated with Increased Body Mass Index - Sarah H. Millan; Mallory L. Hacker; Maxim Turchan; Anna L. Molinari; Amanda D. Currie; David Charles (Parkinson's Disease)
Previous studies suggest that deep brain stimulation of the subthalamic nucleus (STN-DBS) for Parkinson’s disease (PD) leads to weight gain. This study analyzes changes in body mass index (BMI) in 29 subjects from a prospective, single-blind trial of DBS in early stage PD (age 50–75, Hoehn & Yahr stage II off medication, treated with antiparkinsonian medications for ≥6 months but <4 years, and without a history of motor fluctuations, dyskinesias, or dementia). Subjects were randomized to DBS plus optimal drug therapy (DBS+ODT; n=15) or ODT (n=14) and followed for 24 months. Weight and height were recorded at baseline and each follow-up visit and used to calculate BMI. BMIs were compared within and between groups using nonparametric t-tests. Mean BMI at baseline was 29.7 in the ODT group and 32.3 in the DBS+ODT group (p>0.05). BMI change over two years was not different between the groups (p=0.62, ODT = −0.89; DBS+ODT = −0.17). This study suggests that STN-DBS is not associated with weight gain in subjects with early stage PD. This finding will be tested in an upcoming FDA-approved phase III multicenter, randomized, double-blind, placebo-controlled, pivotal clinical trial evaluating DBS in early stage PD (ClinicalTrials.gov identifier NCT00282152).